Analysis Of Food Availability Of Rice Farmer Households In Talang Besar Village Padang Guci Hilir District Kaur District - Distora Prima Prima; Eko Sumartono; Herri Fariadi (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: To evaluate food availability and analyze the factors influencing it in rice farming households in Talang Besar Village, Padang Guci Hilir District, Kaur Regency. Method: The method used is descriptive quantitative with multiple linear regression analysis. The sample consists of 82 respondents, who are active female rice farmers. Data were collected through interviews, direct observation, and secondary data. Results: The average food availability in rice farming households is 1404 kcal/capita/day, which is classified as medium (between 1400–1600 kcal/capita/day). Factors influencing food availability include production factors (X1), rice stock (X2), and harvested area (X3), all of which have a positive impact on food availability. Meanwhile, rice prices (X4) do not have a significant effect on the food availability in farming households. Findings: Rice production, rice stock, and harvested area positively influence food availability, while rice prices do not have a significant effect on food availability. Novelty: This study provides a unique perspective by integrating factors such as rice production and harvest area in the context of food availability in Talang Besar Village. Originality: This research contributes significantly to food security in rural areas, especially among rice farming households in Kaur Regency. Conclusions: Improving food availability should focus on increasing rice production, managing rice stocks, and expanding harvested areas, with further research needed to explore other influencing factors.